A PROSPECTIVE STUDY OF DIETARY ENERGY DENSITY AND WEIGHT GAIN IN WOMEN - Bes-Rastrollo, Maira (2008)
BACKGROUND: Little is known about the long-term effects of dietary energy density (ED) on weight gain. METHODS: We conducted a prospective study of 50,026 women (mean age: 36.5; SD: 4.6) in the Nurses' Health Study II followed from 1991 to 1999. Dietary ED and body weight were ascertained in 1991, 1995, and 1999. Total dietary ED was calculated by dividing each subject's daily energy intake (kcal) by the reported weight (g) of all foods consumed. RESULTS: Dietary ED was positively correlated with saturated fat (r=0.16), trans fat (r=0.15), and the glycemic index (r=0.16), but inversely correlated with vegetable protein (r=−0.30), vegetables (r=−0.27), and fruits (r=−0.17). ED was not significantly correlated with total fat intake (r=0.08). Women who increased their dietary ED during follow-up the most (5(th) quintile) had a statistical significant greater multivariate-adjusted weight gain as compared with those who decreased their dietary ED most (1(st) quintile) (in the 8-y time period: 6.42 kg versus 4.57 kg; p for trend < 0.001). However, the amount of weight change over time varied considerably according to the ED of individual foods and beverages. CONCLUSION: Increases in total dietary ED were associated with long-term weight gain among younger and middle-aged women. However, public health recommendations cannot be made simply based on ED values of individual foods and beverages only. Reducing consumption of foods high in saturated and trans fats and refined carbohydrates and increasing consumption of fruits and vegetables may help to reduce dietary ED and prevent weight gain.